Synergistic Catalytic Effects of Carbon Nanotube and Nano-Sized TiO2 on the Hydrogen Sorption of Magnesium Hydride - Mei-Quiang, Fan; Li-Xian, Sun; Xu, Fen (Asian Journal of Chemistry, 2010)
Different TiO2 such as anatase, rutile and sintered C/anatase were added to magnesium hydride by high-energy ball milling in order to improve the hydrogenation properties of magnesium hydride. The results showed that sintered C/anatase were easily distributed uniform in the MgH2 matrix and resulted in the good hydrogen sorption of magnesium hydride such as the faster kinetic of hydrogenation and good cycling. Its excellent properties came from the synergistic catalytic effect of TiH formed after de/hydrogenation cycles and nano carbon tubes.